Jewish Education from Antiquity to the Middle Ages: Studies in Honour of Philip S. Alexander - Brooke, George J. (Ancient Judaism and Early Christianity Ser, 2017)
Intro -- Contents -- List of Figures and Tables -- Notes on Contributors -- Introduction -- 1 Aspects of Education in the Sectarian Scrolls from the Qumran Caves -- 2 Could Jesus Really Read? Literacy in Roman Galilee -- 3 Paideia in the Fourth Book of Maccabees -- 4 The Shaping of Memory: Josephus on Agrippa II in Jerusalem -- 5 Pedagogues and Primary Teachers, from Paul to the Mishnah -- 6 The Aramaic Targum and its Ancient Jewish Scholarly Environment -- 7 Educational Features in Ancient Jewish Literature: An Overview of Unknowns -- 8 Anecdotal Evidence: Memory, Tradition and Text in Early Christianity and the Hellenistic Schools -- 9 God as the Educator of Humanity: Some Voices from the Syriac Tradition -- 10 Liturgy as an Educational Process in Talmudic and Medieval Judaism -- 11 Learning to Read Biblical Hebrew in the Middle Ages: The Transition from Oral Standard to Written Standard -- 12 Glossary of Difficult Words in the Babylonian Talmud (Seder Moʿed) on a Rotulus -- 13 A Jewish Charm for Memory and Understanding -- 14 Preaching to his Daughter: Jacob Anatoli's Goad for Students (Malmad ha-talmidim) -- 15 Entering the Field of Philosophy: Provence, Mid-Fourteenth Century -- Appendix 1: Philip S. Alexander's Bibliography -- Index of Modern Authors -- Index of Sources -- _GoBack